The Regional Western Sweden SOM Survey 1993 - SOM Institute, University of Gothenburg (University of Gothenburg, 1994)
This is the second study in the series of SOM-surveys carried out in Western Sweden exclusively. The questionnaire was divided into six subject fields: mass media; politics and society; the municipality of Göteborg; energy, nuclear power and environment; leisure and housing; and background. Many of the questions are replications of questions asked in SOM-survey Western Sweden 1992 (SSD 0460), but there is also a number of new questions. These questions dealt with time spent listening to the radio, viewing morning television and reading morning paper; impression of morning television; amount of local government issues read in the local paper; confidence in a number of Swedish mass media; opinion on a number of statements concerning the regional division of Sweden. Respondents living in Göteborg had to answer a number of questions dealing with the magazine ´Vårt Göteborg´, published by Göteborg local authority. Other questions specific for respondents living in Göteborg dealt with the neighbourhood committees and their activities. Respondents also had to give their opinion on a number of proposals concerning local environmental issues. Furthermore they had to indicate how often they had participated in a number of leisure activities the last twelve months.

Purpose:

Study attitudes and behaviors that are linked to local and regional issues and phenomena

Detta är den andra studien i serien SOM-undersökningar genomförda i Västsverige. Undersökningens frågeformulär var indelat i sex områden: massmedia; politik och samhälle; Göteborgs kommun; energi, kärnkraft och miljö; fritid och boende; samt bakgrundsfrågor. Ett stort antal frågor är replikationer av de som ställdes i 1992 års Väst-SOM, men det finns även ett antal nya frågor. En ny fråga behandlar morgonvanor; hur lång tid man ägnar åt radiolyssnande, tittande på morgon-TV och läsning av morgontidning under perioden 5.00-10.00. Andra nya frågor tar upp inställning till morgon-TV, läsning av kommunalt material i den lokala tidningen, förtroendet för ett antal svenska massmedier, inställning till den regionala indelningen, inställning till ett antal förslag att förbättra kommunens miljö samt fritidsaktiviteter under det senaste året. Respondenter bosatta i Göteborg fick också besvara ett antal frågor om den av Göteborgs kommun utgivna informationstidningen 'Vårt Göteborg' samt om stadsdelsnämnderna och dess verksamhet.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
Den västsvenska SOM-undersökningen 1993
Väst-SOM 1993
Keywords: housing; boende; mass media; massmedia; occupations; yrken; public sector; offentlig sektor; energy; energi; environment; miljö; local government policy; kommunalpolitik; voting intention; röstavsikt; environmental degradation; miljöförstörelse; trust; förtroende; political interest; politiskt intresse; local government services; kommunal service; nuclear energy; kärnkraft; newspaper readership; tidnings läsekrets; public services; offentlig service; television channels; tv-kanaler; news; nyheter; income; inkomst; television viewing; tv-tittande; internal politics; inrikespolitik; political parties; politiska partier; regional policy; regionalpolitik; local government; kommunstyrelse; residential areas; bostadsområden; european economic community; europeiska ekonomiska gemenskapen; working conditions; arbetsförhållanden; households; hushåll; leisure time activities; fritidsaktiviteter; educational levels; utbildningsnivå; mass media use; mediaanvändning; energy supply; energiförsörjning; electronic equipment; elektronisk utrustning; radio listening; radiolyssnande; natural energy resources; naturliga energiresurser; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap